‘New’ literacies: technologies and values - Lankshear, Colin; Knobel, Michele (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2012)
It is too easy to make light of ‘new literacies’ by saying things like: “Well, there are always newer ones coming along”. Such remarks suggest new literacies have a similar kind of life trajectory to an automobile: new in 2009, semi-new in 2010, and old hat by 2011. Against this kind of “that’s so yesterday” perspective, we suggest in this article that ‘new literacies’ are best understood in terms of an historical period of social, cultural, institutional, economic, and intellectual change that is likely to span many decades – some of which are already behind us. We associate new literacies with an historical conjuncture and an ascending social paradigm. From this perspective we suggest that the kinds of practices we currently identify as new literacies will cease to be ‘new’ once the social ways characterizing the ascending paradigm have become sufficiently establised and grounded to be regarded as conventional. Furthermore we suggest that at the heart of the idea of new ethos stuff is the idea of technological change aligning with a range of increasingly popular values.